Predicting transporter effects on the pharmacokinetics of metabolized drugs - Estudante, Maria Margarida André Oliveira, 1974- (2011)
Tese de doutoramento, Farmácia (Biofarmácia e Farmacocinética), Universidade de Lisboa, Faculdade de Farmácia, 2011